Gravity Ropeway and Tuin Technology: An Alternative Transportation - Aryal, Sarita; Giri, Shradha (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
No Abstract DOI: http://dx.doi.org/10.3126/hn.v9i0.7081 Hydro Nepal Vol.9 July 2011 79-80